Assessing raw material efficiency and waste management for Sustainable Development: A VIKOR and TOPSIS Multi-Criteria Decision Analysis - Depczyński Radosław (Production Engineering Archives)
This study explores the integration of sustainability in decision-making processes within a steel manufacturing company in Poland. As global clients increasingly demand sustainable practices, companies must adapt their operations to meet these expectations. We applied Multi-Criteria Decision Analysis (MCDA) methods, specifically TOPSIS (Technique for Order Preference by Similarity to an Ideal Solution) and VIKOR (in Serbian: VlseKriterijuska Optimizacija I Komoromisno Resenje), along with three weighting techniques, namely Entropy, Standard Deviation, and CRITIC (Criteria Importance Through Inter-criteria Correlation), to evaluate the sustainability of four products. Nine criteria were considered, including material type, corrosion protection, surface treatment, and various manufacturing processes. Our findings reveal that the MCDA framework effectively ranks products from most to least sustainable, highlighting the importance of raw material efficiency and waste management. This research demonstrates the practical application of MCDA methods in assessing sustainability within the steel industry, providing a basis for future studies to extend this framework to other manufacturing sectors and regions. Overall, this approach supports informed decision-making, aligning with broader sustainability goals while satisfying the demands of business partners and clients.